Proposal for Improving the Work Posture of Stitching Station Operators at CV. Indonesia Jaya Using the Rapid Upper Limb Assessment - Rodhian, Syahrul; Agusti, Febrina; Filemon Waluyono, Garnet (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study evaluates the effectiveness of the Rapid Upper Limb Assessment (RULA) method in improving work posture in industrial settings. Poor posture can lead to musculoskeletal disorders and reduced productivity. Using a quantitative approach, RULA was applied across several production departments, with data collected through direct field observation. The analysis shows that RULA significantly improved work posture, reduced discomfort, and lowered the risk of musculoskeletal injuries. The study supports RULA as an effective tool for posture improvement and recommends integrating regular ergonomic evaluations into work design.